Adrenal insufficiency in acute oral opiate therapy. - Policola, C; Stokes, V; Karavitaki, N; Grossman, A (2014)
UNLABELLED: Opiate drugs such as morphine are in extensive use for pain relief and palliation. It is well established that these drugs can cause changes in endocrine function, but such effects are not always sufficiently appreciated in clinical practice, especially in relation to the hypothalamic-pituitary-adrenal (HPA) axis. Herein, we report on an 18-year-old man who was diagnosed with a slipped left femoral epiphysis following a long history of pain in his leg. On examination, he was thought to look relatively young for his age and therefore the orthopaedic surgeons arranged an endocrine assessment, which showed an undetectable concentration of serum cortisol and a suppressed concentration of testosterone; therefore, he was referred urgently with a diagnosis of hypopituitarism. We elicited a history that he had been treated with opiate analgesics for 3 days at the time of his original blood tests. Full endocrine assessment including a short Synacthen test revealed that he now had normal adrenal and pituitary function. We conclude that his morphine therapy had caused profound suppression of his HPA and pituitary-gonadal axes and suggest that clinicians should be aware of these significant changes in patients on even short-term opiate therapy. LEARNING POINTS: Therapy with opiates is the standard therapy for severe acute and chronic pain.Such drugs cause profound changes in endocrine function.Importantly, opiates suppress the HPA axis at a central level.Short-term therapy with morphine could be the cause of biochemical adrenocortical insufficiency.Morphine and related drugs also suppress the pituitary-gonadal axis.After discontinuation of therapy with such drugs, adrenal function improves.